An introduction to sports coaching : connecting theory to practice. - Jones, Robyn L. (Taylor and Francis, 2013)
An Introduction to Sports Coaching provides students with an accessible and engaging guide to the scientific, social scientific, medical and pedagogical theory that underlies the practice of quality sports coaching. Now in a fully updated and revised second edition, it introduces students to the complex, messy, multi-faceted nature of coaching, and explores the full range of 'knowledges' which inform all successful coaching practice. Written by a team of leading international sports coaching academics and practitioners, as well as sport scientists and social scientists.